2019
DOI: 10.1007/s12687-019-00416-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving follow up after predictive testing in Huntington’s disease: evaluating a genetic counselling narrative group session

Abstract: Recently updated Huntington's disease (HD) predictive testing guidelines emphasise clinicians' responsibility to facilitate emotional support following testing, regardless of the result. Yet models of post-test counselling support are poorly defined. Moreover, it is unclear how these might be best delivered. In this project, a genetic counsellor and clinical psychologist developed standalone group sessions using collective narrative practices for individuals post-predictive testing. Here we present an evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Since 2015 as part of a service improvement, we have been offering Genetic Counseling narrative groups as a stand‐alone session to small groups of patients (MacLeod et al., 2018; Spiers et al., 2020; Stopford et al., 2020).…”
Section: Genetic Counseling Narrative Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2015 as part of a service improvement, we have been offering Genetic Counseling narrative groups as a stand‐alone session to small groups of patients (MacLeod et al., 2018; Spiers et al., 2020; Stopford et al., 2020).…”
Section: Genetic Counseling Narrative Groupsmentioning
confidence: 99%
“…These group sessions were initially offered to patients with a family history of Huntington's disease and subsequently evaluated with other groups of patients including groups for familial cancer, cardiac, and eye genetic conditions (MacLeod et al., 2018; Spiers et al., 2020; Stopford et al., 2020). The aim of these groups is to help support resilience and participants’ own preferred ways of coping.…”
Section: Genetic Counseling Narrative Groupsmentioning
confidence: 99%
“…With regards to this, the adoption of family therapy models (e.g., focused on attachment styles [102,103]) for children and younger individuals affected by HD may be helpful, in particular due to recent evidence showing that the clinical presentation of juvenile HD may be more heterogeneous than previously thought [104]. In addition, as one of the qualitative studies identified by the present review showed preliminary positive results for a group genetic counselling session based on narrative therapy [62], similar forms of support may be explored and adapted for individuals at risk of HD not wishing to undergo genetic testing, Finally, more consideration should be given to investigating how psychological approaches may be adopted across the entire clinical trajectory of HD, from the premanifest phase to stage 5 [105]. Indeed, as severe cognitive deterioration tends to characterise HD's intermediate to advanced stages (e.g., [3][4][5], especially in the domains of language and executive functioning, the opportunity for effective psychological interventions may appear to be relatively limited to prodromal and early stages (e.g., 1-2).…”
Section: Copingmentioning
confidence: 69%
“…Still, no papers examined whether the number of pre- and post-test counseling sessions made a difference to outcomes. One UK series of studies trialed a new practice of support post-testing, with a novel standalone genetic counseling narrative group approach for individuals with a negative HD predictive test result [ 64 ] and a positive HD predictive test result [ 65 , 66 ], as well as their partners [ 66 ]. The majority of participants were positive about the group session being a safe way to share experiences in a structured way [ 66 ], discuss difficult emotions, highlight coping resources, and feeling a sense of community [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…One UK series of studies trialed a new practice of support post-testing, with a novel standalone genetic counseling narrative group approach for individuals with a negative HD predictive test result [ 64 ] and a positive HD predictive test result [ 65 , 66 ], as well as their partners [ 66 ]. The majority of participants were positive about the group session being a safe way to share experiences in a structured way [ 66 ], discuss difficult emotions, highlight coping resources, and feeling a sense of community [ 64 , 65 ]. Barriers to accessing genetic counseling and testing Ten studies described travel distance and time as barriers to accessing genetic counseling or testing [ 33 , 42 , 43 , 47 , 59 , 62 , 67 70 ] or adequate support throughout the process [ 47 ].…”
Section: Resultsmentioning
confidence: 99%